2021
DOI: 10.3390/ijerph18084020
|View full text |Cite
|
Sign up to set email alerts
|

Association between Triglyceride Glucose Index and Corrected QT Prolongation in Chinese Male Steelworkers

Abstract: Objectives: Increased triglyceride glucose (TyG) index appears to be linked to carotid and coronary atherosclerosis and calcifications and possesses an elevated future risk of developing cardiovascular disease. Corrected QT (QTc) interval prolongation is associated with ventricular arrhythmias and sudden cardiac death, and a high prevalence of prolonged QTc interval was previously reported in blue-collar workers. The purpose of this study was to find the possible causal inter-relationship between TyG index and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
5
1
Order By: Relevance
“…In addition, serum concentrations of aspartate aminotransferase (AST), uric acid, and alanine aminotransferase (ALT) were also measured. A parallel, multichannel analyzer (Hitachi 7170A, Tokyo, Japan) was used for all measurements [ 22 ], and an automated cell counter (XE-2100, Sysmex Corp., Kobe, Japan) was used to measure the peripheral leukocyte count. The CKD-EPI study equation was used to assess renal function (estimated glomerular filtration rate [eGFR]) in our male blue-collar workers as follows [ 23 ]: GFR = 141 × min(S cr /κ, 1) α × max(S cr /κ, 1) −1.209 × 0.993 Age , where S cr is serum creatinine (mg/dL); κ is 0.9; α is −0.411, and min/max indicate the minimum/maximum of S cr /κ or 1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, serum concentrations of aspartate aminotransferase (AST), uric acid, and alanine aminotransferase (ALT) were also measured. A parallel, multichannel analyzer (Hitachi 7170A, Tokyo, Japan) was used for all measurements [ 22 ], and an automated cell counter (XE-2100, Sysmex Corp., Kobe, Japan) was used to measure the peripheral leukocyte count. The CKD-EPI study equation was used to assess renal function (estimated glomerular filtration rate [eGFR]) in our male blue-collar workers as follows [ 23 ]: GFR = 141 × min(S cr /κ, 1) α × max(S cr /κ, 1) −1.209 × 0.993 Age , where S cr is serum creatinine (mg/dL); κ is 0.9; α is −0.411, and min/max indicate the minimum/maximum of S cr /κ or 1.…”
Section: Methodsmentioning
confidence: 99%
“…As steel industry in an important pillar industry in China, the health of steelworkers cannot be ignored. According to related studies, steelworkers may have a higher prevalence of CAS compared with the general population due to their exposure to special risk factors such as high temperature, noise, and shift work in the production environment [ 16 , 17 , 18 , 19 ]. Therefore, it is particularly important to find a simple and effective predictor.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Bos et al found that serum and hepatic triglyceride levels were in patients with short sleep duration, but the significance disappeared after adjusting for BMI and sleep apnea. 38,41 Although there was no difference between the groups in the BMI values, and patients with sleep apnea were not included in our study, serum triglyceride levels were higher in the insomnia group. The possible mechanism, as shown in a previous study, may be due to the fact that shorter sleep times alter serum leptin and ghrelin levels, and to patients' excessive tendency to consume carbohydrate-rich foods and increased insulin resistance.…”
Section: Discussionmentioning
confidence: 70%
“…In a recent study, Lee et al . have revealed a significant relationship between high triglyceride levels and QTc 38 . Furthermore, the previous studies demonstrated that arrhythmias are related to proinflammatory cytokines such as interleukin 6 and C‐reactive protein by the modulation of ion‐channel function 39,40 and aggravation of the sympathetic system 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation